Accountability And Financial Performance ofLocal Government in Indonesia - Aminah AMINAH; . Lindrianasari (UBL, 2013)
This study aimstodetermine the relationshipof accountability forthe performanceof LKPD as reflected by WTPopiniongiven bytheSupreme Audit Agency(BPK). The sample usedin this studyisas much as1,238local governmentfinancial datainIndonesiaduring the period of 2009-2011. Statisticaltoolusedinthetesting ofhypothesisis logisticregressionanalysis. Results of this studyindicatethataccountability(measured using the budgetvariance) is positively related tothe performance ofthe financial statements. This resultindicatesthat the smallerthe difference inthe budgetwiththe realizationorganizedby local governmentin the earlyyears, the better theperformance ofthelocal government finance.